2014
DOI: 10.1590/s0100-736x2014000400004
|View full text |Cite
|
Sign up to set email alerts
|

Beta-lactamase detection in Staphylococcus aureus and coagulase-negative Staphylococcus isolated from bovine mastitis

Abstract: Pesq. Vet. Bras. 34(4):325-328, abril 2014 325 RESUMO.-[Detecção de beta-lactamase em Staphylococcus aureus e Staphylococcus coagulase negativa isolados de mastite bovina.] Os objetivos do presente estudo foram avaliar a presença/produção de beta-lactamases por ambos os métodos fenotípicos e genotípicos, verificar se os resultados são dependentes do tipo de bactéria (Staphylococcus aureus contra Staphylococcus coagulase negativa -CNS) e verificar a concordância entre os testes. Um total de 200 amostras ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
(20 reference statements)
3
6
1
1
Order By: Relevance
“…Although all isolates in the present investigation were phenotypically resistant to penicillin and ampicillin, the bla Z gene was detected in only one isolate (2.6%), showing discrepancy between phenotypic resistance and detection of β-lactamase gene bla Z. β-lactamase phenotype could be the result of expression of more than one gene. Moreover, there is more than one mechanism that grant staphylococci β-lactam resistance other than the expression of bla Z gene [32]. On the contrary, previous studies found higher prevalence (23.0% and 20.0%) for the bla Z gene in CoNS isolated from mastitis in cattle in Argentina [33].…”
Section: Discussionmentioning
confidence: 99%
“…Although all isolates in the present investigation were phenotypically resistant to penicillin and ampicillin, the bla Z gene was detected in only one isolate (2.6%), showing discrepancy between phenotypic resistance and detection of β-lactamase gene bla Z. β-lactamase phenotype could be the result of expression of more than one gene. Moreover, there is more than one mechanism that grant staphylococci β-lactam resistance other than the expression of bla Z gene [32]. On the contrary, previous studies found higher prevalence (23.0% and 20.0%) for the bla Z gene in CoNS isolated from mastitis in cattle in Argentina [33].…”
Section: Discussionmentioning
confidence: 99%
“…The results of antimicrobial susceptibility test showed that the bacteria are resistant to all β-lactam antibiotics and oxacillin. For β-lactamase production, different phenotypic diagnostic methods that are specific and reliable such as the clover leaf and iodometric methods were used (Robles et al, 2014). The iodometric method was considered as an accurate method (Devapriya et al, 2013) while, the clover leaf method was considered as a reliable method for investigating β-lactamase production in staphylococci (Bergan et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Beta-lactam compounds such as penicillin continues to be one of the most frequently used drugs in veterinary medicine (Robles et al, 2014). And it is recommended as the first choice for bacteria that are inherently sensitive to it.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore the emergence of other species besides Staphylococcus aureus as human pathogens, as well as, reservoirs of antimicrobial resistance and other virulence factor, increases the necessity in the developing of reliable methods for the most frequent species identification, to establish the pathogen-host relationship, as well, development of epidemiological approaches (Silva et al 2013, Silva et al 2014, Robles et al 2014). …”
Section: Introductionmentioning
confidence: 99%